Hauling efficiency in Matang Mangrove Forest Reserve - Nordin, Muhammad Hisyam (2018)
Matang mangrove forest is sustainably managed for its timber production purposes. Harvesting operation in this mangrove forest is challenging due to topographical and work environment condition. Muddy soil and the need of preserving the rich ecosystem in the mangrove forest have made mechanized skidding unsuitable to be applied during the harvesting process. Coherently, the increased demand of charcoal production has forced the charcoal factory owners to find ways in improving their timber transportation system. Log hauling is the only appropriate method in extracting timber out to log pond in mangrove forest timber production. This study was carried out to investigate timber productivity and time of extraction process as well as performance of hauling operation using wheelbarrow. Travel time data from the ten trips of hauling cycle was recorded. Manual hauling method consists of four main work elements which were return, loading, hauling with load, and unloading. Factors of the delay also were recorded. Regression analysis was performed to examine the relationship between time and productivity of timber production. Results of hauling extraction system showed that the effective log amount was eight, with 123 meters efficient hauling distance. Loading time had shown the longest time (28%), hauling with load (23%), return (20%), and unloading (19%). However, hauling performance and productivity were slightly affected by the factor delays that occurred during the operation. The main delay was caused by personal delay (10%), which was the least in time consumption.